Ground- and excited-state reactivity of iron porphyrinogens - Bachmann, Julien; et al. (Inorganic Chemistry, 2007)
The iron(II) porphyrinogen dication, [(LFeII)-Fe-Delta Delta](2+), is a multielectron oxidant featuring the metal center in its reduced state and the ligand as the redox reservoir. Oxidations break the ligand's redox-active C-C bonds. Extremely short-lived excited states are consistent with extensive structural reorganization that accompanies charge-transfer excitation of the porphyrinogen.